1963
DOI: 10.1073/pnas.50.5.885
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Hemoglobin in Primates

Abstract: Several proposals have been made to describe the evolutionary relationships among the genes that control the structure of the polypeptide chains in the normal human hemoglobins.1-3 At present, the best means for evaluating these proposals is by analysis of the sequence of amino acids in the polypeptide chains of hemoglobins from several vertebrate and invertebrate forms. With this information, homologies of chain structure as shown by correspondence between sequences of amino acids in entire chains, or portion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1966
1966
1985
1985

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Precedents exist for this line of reasoning, since there is now considerable evidence that gene reduplication was a common means of genetic diversification during evolution in the vertebrate line (21). The analogy between the present findings and those described earlier for immunoglobulin (22), hemoglobin (23), and haptoglobin (24) evolution is obvious.…”
Section: Residuessupporting
confidence: 58%
“…Precedents exist for this line of reasoning, since there is now considerable evidence that gene reduplication was a common means of genetic diversification during evolution in the vertebrate line (21). The analogy between the present findings and those described earlier for immunoglobulin (22), hemoglobin (23), and haptoglobin (24) evolution is obvious.…”
Section: Residuessupporting
confidence: 58%
“…Perhaps the ideal method is the determination of the amino acid sequences of homologous proteins, as has been begun in cytochrome c (Margoliash, 1963;Smith and Margoliash, 1964) and in hemoglobin (Braunitzer et al, 1964;Hill et al, 1963;Hill and Buettner-Janusch, 1964), but this involves a very great deal of time and work and might fairly be characterized as cumbersome, and therefore not a choice method for extensive comparisons and surveys. The existence of such techniques has in turn interested evolutionary biologists in their possible applications.…”
mentioning
confidence: 99%
“…Thus the evolution of the neurohypophysial hormones may have taken place along the same lines as the evolution of proteins [e.g. haemoglobins (Ingram, 1962;Hill, Buettner-Janush & Buettner-Janush, 1963)]. The identity of the precursor of arginine vasopressin is not exactly known but Sachs & Takabatake (1964) suggested that it is a protein, from which the hormone is split off.…”
Section: Introductionmentioning
confidence: 97%